Analysis of Nursing Management Unstable Blood Glucose Levels in Type 2 Diabetes Mellitus Patients - Sulastri Sulastri; Harjati Harjati (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2022)
Background: Diabetes Mellitus (DM) is a clinical syndrome of impaired metabolic secretion, insulin action, or both characterized by hyperglycemia. Various nursing problems can occur due to hyperglycemic conditions that are not handled properly. The instability of blood glucose levels is a major problem that occurs in uncontrolled DM patients. This condition can lead to various complications and complications so comprehensive treatment management is needed. Objectives: This study aims to explore and analyze the nursing management of unstable blood glucose levels in type 2 DM patients who were hospitalized. Methods: This study is a qualitative study using an exploratory case study method in diabetes mellitus patients type 2 who were hospitalized. The data obtained were processed and analyzed based on theories that explain the occurrence of the problem of instability in blood glucose levels and the nursing management carried out in patients with type 2 diabetes mellitus. Results: The results of this study indicate that the main problem in patients with type 2 diabetes mellitus is the instability of blood glucose levels which is characterized by hyperglycemia. Nursing management carried out is monitoring blood glucose level laboratory results, management of hyperglycemia, medication management, nutrition/diet management, treatment, and care education programs can reduce blood glucose levels. Conclusion: The problem of blood glucose instability is a priority problem in type 2 diabetes mellitus and comprehensive nursing management will determine the success of controlling blood glucose levels so that they are normal and stable.